Knowledge, awareness, and attitudes of female sex workers toward HPV infection, cervical cancer, and cervical smears in Thailand - Kietpeerakool C. (2014)
Objective: To determine the knowledge, attitudes, and awareness of female sex workers (FSWs) regarding cervical cancer and its prevention in Thailand. Method: From August through November 2008, 402 consecutive FSWs were recruited for interviews. Results: The mean knowledge score was 4.9 (maximum possible, 15; range, 0-14). Approximately 60% of the FSWs had knowledge scores less than 5. Low education and a lack of health insurance were significant independent predictors of low knowledge scores (adjusted odds ratios, 3.17 and 1.97, respectively). More than half of the FSWs were unaware of being at higher risk for HPV infection or of the possible consequences of HPV infection. The negative attitude regarding cervical screening was caused by the fear of abnormal results (27.9%), experiencing pain (18.4%), and embarrassment (14.7%). Conclusion: The knowledge and awareness of HPV infection, cervical cancer, and utility of cervical smears is low among FSWs in Thailand. Designing and implementing effective interventions is crucial and merits attention in future research. © 2009 International Federation of Gynecology and Obstetrics.